Disabled Capital: A Narrative of Attention Deficit Disorder in the Classroom Through the Lens of Bourdieu’s Capital - Jared David Berezin (Disability Studies Quarterly, 2014)
Within each socio-economic class there exist able classes, characterized by the ability to successfully access and enact their preferred capital. There also exist disabled classes of individuals who possess preferred capital, but remain unable to perform in the same manner as able bodies. In the attempt to perform accumulated knowledge and normality, the disabled individual confronts the relationship between his capital and body, his intention and ability. By examining my own classroom experience as a student with attention deficit disorder, together with research from the fields of education and disability studies, this research-based narrative reveals that preferred capital does not merely comprise cultural knowledge and social relationships, but also the ability to perform one's knowledge and desires through behavior that is valued in the classroom. In a field dominated by able-bodied individuals, the disabled body possesses "disabled capital", as preferred capital becomes compromised when housed within a disabled body.
Keywords: ADHD; ADD; Bourdieu; capital; disability; performance